STUDENT’ANXIETY IN LEARNING SPEAKING - Yasti Januariza; Suswati Hendriani (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Speaking is one of the important skills that students  should master.  in  order that  they are able to deliver their ideas. To master the skill, the students, certainly, should have much practice, should  be self-confident, not be nervous, no be anxious,  must be brave, enjoy  speaking. In reality, many students are too anxious and   do not enjoy learning speaking. They try to finish speaking practices as soon as possible when they get turn to speak or be  the  last performer.  They try to memorize all of materials before entering speaking classes to  avoid making  a mistake. Unfortunately, the lecturer who teaches Speaking subject,  do not know the personality of his students very well. Thus, he forces the students who are not ready yet to speak up. Consequently, they  lose their ideas or decide not to speak even when  their lecture asks them to do it.  Why are the students reluctant to speak was found through  a qualitative research. The informants of the research are  the students of English Teaching Department of State Institute for Islamic Studies (IAIN) Batusangkar. The technique of data collections are  a open-ended  questionnaire and  in-depth  interview. The results of the research show the  causes of the students’ anxiety are:  fear of mistake, fear  of being laughed  at or mocked,  lack of ability,  lack of  preparation, lack of practice, lack of vocabulary, lack of self-confidence, lack of conviction, lack of motivation, shyness, not liking the  speaking subject, the  teacher’s teaching   method,  and  the teachers’  attitude and behavior.